The relationship between mindfulness and work-life balance: The mediation role of emotional regulation - Muharrani, Tis'a; Lubis, Rahmi; Hardjo, Suryani (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
Air Traffic Controller (ATC) is one of the occupations in the service sector. ATC, like other jobs, has other social tasks outside of work that require the ability to balance work and family or personal and social responsibilities (i.e., work-life balance). This research aims to test the role of emotional regulation in mediating the relationship between mindfulness and work-life balance among ATC officers. This research was conducted quantitatively. The data was collected through the work-life balance, emotion regulation, and mindfulness scales and was analyzed using structural equation modeling (SEM) operated through the JASP program version 16. 172 employees (59% males) involved in this research. Results showed that emotional regulation significantly mediates the relationship between mindfulness and work-life balance. This indicates that ATC officers with a mindful condition will consciously be able to direct their attention to focus on the current situation and role. This will affect ATC's ability to manage cognitively to provide emotional responses and express emotions according to the needs of the current situation in completing the role at hand and achieving work-life balance. This finding has implications on how management might assist ATC officers in improving work-life balance by enhancing emotional regulation skills and mindfulness.